AKTIVITAS MEREMAS UNTUK MENINGKATKAN MOTORIK HALUS ANAK KELOMPOK A - Nofi Yanti; Ika Anggraheni; Ari Kusuma Sulyandari (Jurnal Dewantara, 2022)
This classroom behavioral survey aims to determine teachers' and children's activities squeezing or coloring pictures and describe the improvement of developing fine motor abilities using squeezey things picture-matching activites in group A, youngsters in PAUD Al-Amin. Research subick was 11 children in group A in PAUD Al-Amin. The data collection techniques used in this study were observations by researchers and documentation of children's learning activities in the form of photographs. Analytical The technique used in this study is descriptive analysis. Results showed improvement in children's fine motor skills, namely developing according to expectations. Based on analysis of cycle I and II results, squeezing activities with drawing coloring activities can improve children’s fine motor skill.